Netflix and Qwikster ; would success in DVDs lead to success in streaming? - Oster, Sharon M.; Chen, M. Keith; Rosenthal, Jean W., 1945- ([London] : SAGE, 2016)
In 2011, Netflix announced changes that observers characterized as among the greatest missteps in the history of corporate strategy. First, the company significantly raised prices. Then, Reed Hastings, the founder and CEO of Netflix, described plans to split the company between streaming and disc rental, spinning off the DVD-rental business to a new entity called Qwikster. The outrage from customers and investors was extreme. Within two weeks, Hastings reversed the plan to split the company (though maintaining the price increases). During the debacle, Netflix lost 2 million subscribers and the stock dropped more than 75 percent in value. This case study discusses this topic.
Originally Published in: Oster, S. M., Chen, M. K., & Rosenthal, J. W. (2012). Netflix and Qwikster: Would Success in DVDs Lead to Success in Streaming? 12-019. New Haven, CT: Yale School of Management, Yale University.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; Netflix (Firm); Organizational change -- Management -- Case studies; Leadership -- Case studies; Crisis management -- Case studies